2016
DOI: 10.3390/ijerph13080766
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hepcidin and Ferroportin in the Placenta, and Ferritin and Transferrin Receptor 1 Levels in Maternal and Umbilical Cord Blood in Pregnant Women with and without Gestational Diabetes

Abstract: Background: Regulation of iron transfer from mother to fetus via the placenta is not fully understood and the relationship between stored iron status in the mothers’ serum and gestational diabetes (GDM) in case–control studies is controversial. The present study aimed to detect circulating soluble transferrin receptor (sTfR) and ferritin levels in maternal and umbilical cord blood. We also examined the expression of hepcidin (Hep), transferrin receptor (TfR1), and ferroportin (FPN) in the placenta in pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
2
9
0
2
Order By: Relevance
“…The high concentrations of hepcidin and ferritin measured here in cord blood are in accordance with previous observations [20][21][22][23][24][25][26][27][28][29][30]. Nevertheless, there are a handful of previous studies [21,24,31,32] involving measurements of S-hepcidin, sTfR, and S-ferritin sampled in late pregnancy as well as in cord blood. However, only two of these studies did include IL-6 [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…The high concentrations of hepcidin and ferritin measured here in cord blood are in accordance with previous observations [20][21][22][23][24][25][26][27][28][29][30]. Nevertheless, there are a handful of previous studies [21,24,31,32] involving measurements of S-hepcidin, sTfR, and S-ferritin sampled in late pregnancy as well as in cord blood. However, only two of these studies did include IL-6 [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…The staining intensity of FPN in the duodenum biopsy tissues was evaluated by the immunohistochemical score. The method was described previously [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In women that develop gestational diabetes, the most common metabolic disorder during pregnancy that favors a pro-inflammatory state, it has been found that iron overload and iron metabolizing disorders are often associated with glucose-related imbalances. [63][64][65][66] Further studies are necessary to fully understand why only GMAW-MS-exposed cells had significant increases in IL-6 and IL-8, since GMAW-SS also contained Fe, but did not cause increased cytokine production.…”
Section: Discussionmentioning
confidence: 99%